Overview of Breast Examination Screening in Labuhan Haji and Pengadangan Village East Lombok Regency - Reny Apryani; Fathul Djannah; Arif Zuhan (Jurnal Biologi Tropis, 2023)
Breast lump is a condition that is often experienced by many women. Breast cancer is ranked second after cervical cancer which is most common suffered by women in the world. This article was written with the aim of early detection of breast lumps and the number of cancer cases. The subject of this study was a ≥18-year-old woman in Labuhan Haji Village and Pengadangan East Lombok Regency. This study used a non-analytical obssional descriptive method using a cross-sectional study. The data that has been obtained will be analyzed descriptively in the form of diagrams. The results of this study can be concluded ingeneral that the type of lump neoplasma found FAM (Fibroadenoma) which is as many as 7 respondents compared to other types of tumors. The type of non-neoplasma lump that was found in this study was Fibrocystic disease or commonly called fibrostic as many as 6 respondents. Mammae aberans were found in this study, namely as many as 2 respondents aged 53 and 60 years. Ductal Carcinoma or breast cancer with ductal type as many as 1 respondent with the age of 60 years. Ginecomastia there was 1 male respondent aged 33 years.Each tumor in the breast has a tendency to occur in a certain age range and each tumor in the breast has a type of benign and malignant tumor.